Proceso de atención de enfermería en gestante con 25 años de edad de 30 semanas de gestación con polidramnios. - Quijije Zambrano, Santiago Javier (2020)
Polyhydramnios is defined as a pathological accumulation of amniotic fluid secondary to an increase in production or deficiency in elimination, which is why there has been a respectively frequent pathology in obstetrics that can bring complications to pregnancy depending on the degree of severity. Due to its evolution, it will be classified as acute and chronic. The acute stage is sudden onset and appears in the second trimester, when associated with congenital malformations not compatible with life and evolving to a previous delivery. While the chronic degree appears in the third trimester, it is associated with maternal factors and is mainly idiopathic. Regarding its clinical manifestations, the patient will present a progressive and rapid increase in his height of the uterine fundus (AFU), symptoms of compression and / or distension, as he may also notice respiratory distress, lower limb edema, edema. vulvar and abdominal cut, weight gain, development of pre-eclampsia. The diagnosis will be based on a higher AFU for gestational age, difficulty palpating fetal parts, difficulty auscultating fetal focus, and subjective palpation of increased amniotic fluid. However, ultrasound will provide the diagnosis with the measurement of amniotic fluid, the most frequently detected technique is that of Phelan. The treatment is based on the use of indomethacin, but it has now been implemented as an invasive procedure, amniocentesis. The present structured investigation in this clinical case, will provide us with the necessary and correct information, to know the importance of this pathology and to carry out the nursing care provided by the 25-year-old pregnant woman with 30 weeks of gestation with a medical diagnosis of polyhydramnios.